Current and future directions of multimedia technology in tourism. (8th March 2010) - Kanellopoulos, Dimitris N.
The future of tourism organisations and enterprises will be information-oriented, knowledge-driven and much of their daily processes will be automated around the internet. The internet, including multimedia, has provided tremendous potential for remote integration and collaboration in business applications. This paper attempts to provide a review of the application of multimedia technology in tourism environments. It justifies the application of multimedia in various tourism sub-domains such as tourism marketing, tourism education, mobile learning for travellers, mobile tourism guides, multimedia kiosks, virtual museums, virtual tours, multimedia travel plans, cooking studios based on web recipes, video conferencing and modelling demand for space tourism services. A conceptual framework for the design of multimedia systems for tourism is presented and discussed. Future research directions are also proposed.